Analysis of the Influence of Price, Promotion and Company Image on Decisions on Using Winnie's Wedding Organizer & Decoration Services in Sukabumi City - Saepudin Ciamis; Aryanti Ratnawati; Vanny Decianita (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2021)
This study aims to examine the relationship between price, promotion and corporate image on the decision to use Winnie's Wedding Organizer & Decoration services in Sukabumi City. The research was conducted on Winnie's Wedding Organizer & Decoration service users in Sukabumi in the period 2017 - 2019, with a sample of 86 customers. The hypothesis formulated in this study is as follows: